LRRK2 Controls an EndoA Phosphorylation Cycle in Synaptic Endocytosis. - Matta, S.; Van Kolen, K.; da Cunha, R.; van den Bogaart, G.; Mandemakers, W.; Miskiewicz, K.; De Bock, P.J.; Morais, V.A.; Vilain, S.; Haddad, D.; Delbroek, L.; Swerts, J.; et al. (Neuron, 2012)
LRRK2 is a kinase mutated in Parkinson's disease, but how the protein affects synaptic function remains enigmatic. We identified LRRK2 as a critical regulator of EndophilinA. Using genetic and biochemical studies involving Lrrk loss-of-function mutants and Parkinson-related LRRK2(G2019S) gain-of-kinase function, we show that LRRK2 affects synaptic endocytosis by phosphorylating EndoA at S75, a residue in the BAR domain. We show that LRRK2-mediated EndoA phosphorylation has profound effects on EndoA-dependent membrane tubulation and membrane association in vitro and in vivo and on synaptic vesicle endocytosis at Drosophila neuromuscular junctions in vivo. Our work uncovers a regulatory mechanism that indicates that reduced LRRK2 kinase activity facilitates EndoA membrane association, while increased kinase activity inhibits membrane association. Consequently, both too much and too little LRRK2-dependent EndoA phosphorylation impedes synaptic endocytosis, and we propose a model in which LRRK2 kinase activity is part of an EndoA phosphorylation cycle that facilitates efficient vesicle formation at synapses.